Bibliography of Armenian numismatics (2008-2013) - Vardanyan, Aram R. (ՀՀ ԳԱԱ հրատ.)
This list includes books, articles and reviews dealing with Armenian numismatics from the ancient times up to the 19th century. The works related to Armenian numismatics indirectly (mainly archaeological studies or publications where the coinage of Armenia is discussed insufficiently) were not included in this list. It also lacks information on Armenian banknotes and contemporary medals. I will be happy with receiving additional information on the topic.
Keywords: General Bibliography; Numismatics; Bibliography; Auxiliary Sciences of History